2020
DOI: 10.1111/jvim.15775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amoxicillin‐clavulanic acid on clinical scores, intestinal microbiome, and amoxicillin‐resistant Escherichia coli in dogs with uncomplicated acute diarrhea

Abstract: Background: Despite limited evidence of efficacy, antibiotic treatment is still frequently prescribed in dogs with uncomplicated acute diarrhea (AD).Objective: To assess whether amoxicillin-clavulanic acid has a clinical benefit, an effect on the fecal microbiome, and the proportion of amoxicillin-resistant Escherichia coli in dogs with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 66 publications
(152 reference statements)
8
61
0
Order By: Relevance
“…Antibacterials still represent a treatment option for AD, although both in human and veterinary medicine it has been widely demonstrated that their administration in uncomplicated cases is often unnecessary and negatively impacts the gut microbiota composition [ 6 ]. Thus, it is generally suggested that their use should be limited only in those cases presenting sepsis or at clear risk of sepsis [ 6 , 10 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibacterials still represent a treatment option for AD, although both in human and veterinary medicine it has been widely demonstrated that their administration in uncomplicated cases is often unnecessary and negatively impacts the gut microbiota composition [ 6 ]. Thus, it is generally suggested that their use should be limited only in those cases presenting sepsis or at clear risk of sepsis [ 6 , 10 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As regards antibacterial administration in canine acute diarrhea, it should be properly evaluated on a case-by-case basis, as it has been recently reported in a chronic disorder [ 30 ]. Different molecules (e.g., amoxicillin/clavulanic acid, and metronidazole) have been studied over time in AD, and it is now generally accepted that their use should be mainly reserved for those cases presenting sepsis, or at a clear risk of sepsis (evidence of infection associated to systemic inflammatory response syndrome) [ 5 , 6 , 10 , 54 , 55 , 56 ]. For instance, it has been shown that the administration of amoxicillin/clavulanic acid in dogs presenting with acute hemorrhagic diarrhea did not significantly improved parameters, such as severity of clinical signs, fecal consistency, and time of hospitalization, if compared with a placebo group [ 54 ].…”
Section: Traditional Therapeutic and Nutritional Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the clinical benefit of the ADPP was relatively minor overall, the ADPP offers an advantage over other treatments commonly used for managing acute diarrhea, such as antimicrobials and dietary modification, which lack evidence for their efficacy. Few studies demonstrate the efficacy of dietary modulation with either proprietary or home‐cooked diets, and some evidence suggests that antimicrobial treatment is not effective in dogs with acute diarrhea . The ADPP could decrease antimicrobial usage both by a shift in prescribing habits away from the use of antimicrobials in favor of the ADPP in dogs with acute diarrhea and by a decrease in antimicrobial use in those dogs given the ADPP that would otherwise have required AMI.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of dogs with acute diarrhea in the United Kingdom, the most common treatments were dietary modification (66% of cases) and antimicrobial treatment (63% of cases) . Previous studies have reported that up to 71% of dogs with acute diarrhea are treated with antimicrobials despite emerging evidence that antimicrobial treatment is not effective in dogs with hemorrhagic or uncomplicated acute diarrhea . Consequently, acute diarrhea represents a considerable portion of antimicrobial usage in veterinary practice.…”
Section: Introductionmentioning
confidence: 99%